2013
DOI: 10.1021/ol4014969
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Mediated Aliphatic C–H Oxidation with Oximes and Hydrazones

Abstract: A method for aliphatic C-H bond oxidation of oximes and hydrazones mediated by 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) has been developed, which enables the concise assembly of substituted isoxazole and pyrazole skeletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 54 publications
0
73
2
Order By: Relevance
“…The structures of compounds 2 j and 2 k were confirmed by singlecrystal X-ray diffraction studies. [13] On the other hand, the 1,5-H shift involving the N 1 atom, which occurs under other circumstances, [3b, 14] was not observed in the present case, because it is much less favored than the 5-exo-trig cyclization at the N 2 atom. When hydrazones 1 q and 1 r were utilized in the reaction, azomethine imines were formed as spiro compounds in excellent yields ( Table 2, entries 8 and 9).…”
Section: Angewandte Chemiecontrasting
confidence: 59%
“…The structures of compounds 2 j and 2 k were confirmed by singlecrystal X-ray diffraction studies. [13] On the other hand, the 1,5-H shift involving the N 1 atom, which occurs under other circumstances, [3b, 14] was not observed in the present case, because it is much less favored than the 5-exo-trig cyclization at the N 2 atom. When hydrazones 1 q and 1 r were utilized in the reaction, azomethine imines were formed as spiro compounds in excellent yields ( Table 2, entries 8 and 9).…”
Section: Angewandte Chemiecontrasting
confidence: 59%
“…Chiba and co-workers showed that the reaction between the N À H bond in hydrazone 235 and TEMPO can generate anitrogen radical (Scheme 45). [123] Although the nitrogen radical generated in this case is stabilized by the a-nitrogen atom, the equilibrium between the nitrogen radical 237 and the alkyl radical 238 provides alow concentration of the alkyl radical. Thet rapping of the alkyl radical by TEMPO results in the formation of aC ÀOb ond.…”
Section: Abstraction Of Hydrogen Atomsmentioning
confidence: 97%
“…In the example described by Chiba and co-workers,where TEMPO was used to generate an oxygen radical through hydrogen atom transfer from the O À Hbond of an oxime,intramolecular oxygenation of the CÀHbond is observed (Scheme 56). [123] In this system, TEMPO abstracts ah ydrogen atom from oxime 312 to give oxygen radical 314.The alkyl radical 315 formed by 1,5-HAT In almost all the reactions in which an O À Hbond is used to generate an oxygen radical, intramolecular C À Oo xygenation occurs to give afive-membered oxygen heterocycle.The only exception has been reported by Ryu, Sonoda, and coworkers,w here ah igh pressure of CO is applied under the reaction conditions such that alkyl radical 322 undergoes carbonylation before it is oxidized. Theo xidation yields acylium ion 324 and affords g-lactone 321 after cyclization (Scheme 57).…”
Section: Free Alcohols As Precursorsmentioning
confidence: 99%
“…[4][5][6] In β-sp 3 -C-H oxygenation with oximes (X = O), the process is initiated by a 1,5-H-radical shift of the putative oxime O-radicals I, giving β-C-radicals II that are subsequently trapped with TEMPO. The resulting β-aminoxyl oximes III undergo elimination of 1-hydroxy-2,2,6,6-tetramethylpiperidine (TEMPO-H) to form α,β-unsaturated oximes IV that finally cyclize to deliver dihydroisoxazoles.…”
mentioning
confidence: 99%
“…The method allowed us to construct spirocyclic dihydropyrazole 5e in 62% yield (entry 3). The reactions of α-mono-substituted-γ,δ-unsaturated hydrazones 3f-h proceeded in a diastereoselective manner, delivering 4,5-transdihydropyrazoles 5f-h in good to moderate yields (entries [4][5][6]. It is worth noting that hydrazone 3h having allylic (marked in red) and benzylic (marked in green) C-H bonds exclusively selected allylic one (entry 6).…”
mentioning
confidence: 99%